IT non-conformity in institutional environments: E-marketplace adoption in the government sector - Standing, C.; Sims, I.; Love, Peter (Elsevier BV, 2009)
Institutional authority is a factor that impacts adoption of IT. Institutional theory incorporates three different but complimentary perspectives and we used these to develop a layered analysis of IT adoption in organizations. We used a case study of State Government agencies in Australia to show how layers of authority influenced the adoption or rejection of technology and that such forces varied in their influence over time. Based on this, we proposed the notion of patterns of conformity and non-conformity which recognise the changes in levels of compliance over time as organizational forces arise. In particular, the alignment of layers of authority acts to ensure conformity with or rejection of IT adoption decisions.